2018
DOI: 10.1103/physrevb.98.205125
|View full text |Cite|
|
Sign up to set email alerts
|

Large anomalous Nernst coefficient in an oxide skyrmion crystal Chern insulator

Abstract: A sizable transverse thermoelectric coefficient N , large to the extent that it potentially serves applications, is predicted to arise, by means of first-principles calculations, in a Skyrmion crystal assumed on EuO monolayer where carrier electrons are introduced upon a quantum anomalous Hall insulating phase of Chern number C = 2. This encourages future experiments to pursue such an effect.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…For example, in another system, a theoretical model of EuO, which is a ferromagnetic semiconductor, was reported to obtain |N| ∼ 20 μV K -1 for τ = 100 fs. 9) In this case, θ H S 0 was dominant to N, close to the τ = 1 ps cases in our system. In a ferromagnetic semiconductor, Ga 1−x Mn x As, N ∼ 10 μV K -1 was observed.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…For example, in another system, a theoretical model of EuO, which is a ferromagnetic semiconductor, was reported to obtain |N| ∼ 20 μV K -1 for τ = 100 fs. 9) In this case, θ H S 0 was dominant to N, close to the τ = 1 ps cases in our system. In a ferromagnetic semiconductor, Ga 1−x Mn x As, N ∼ 10 μV K -1 was observed.…”
supporting
confidence: 72%
“…Based on this mechanism, a giant |N| was predicted in the monolayer model of a ferromagnetic semiconductor. 9) Recently, it has been predicted that van der Waals MnBi 2 Te 4 having an odd (⩾3) number of septuple layers (SLs) is a ferrimagnetic semiconductor with a large S 0 and nonzero σ xy , [10][11][12] and quantized σ xy has been experimentally observed at 5SLs. 13) Thus, a large |N| originating from |θ H S 0 | can be obtained.…”
mentioning
confidence: 99%
“…36 We have previously used this method successfully to study the thermoelectric properties of half-Heusler compounds and skyrmion crystals. 3,10,36…”
Section: Methodsmentioning
confidence: 99%
“…9 The 2D skyrmion material such as an EuO monolayer is predicted that it has shown a large ANC. 3,10 In 2D materials, the ANE is related to the quantum anomalous Hall effect; this effect, in turn, is determined by the quantized anomalous Hall conductivity (AHC), which can be expressed as σxy = e 2 h C, where C is the Chern number. The quantized AHC was confirmed experimentally by Chang et al 11 in a magnetically doped thin film of a topological insulator (Bi,Sb) 2 Te 3 , suggesting that it is possible to obtain a large ANC in 2D systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus for many materials, α ij /T is a constant at T → 0. However, recently, it has been found that α ij /T diverges at low temperatures in several ferromagnets which exhibit a large ANE 1,18,[20][21][22]24,25 . We show that this peculiar behavior can be understood in terms of D NL : The energy dependence of σ ij (0, ε) is singular at ε = E VHS where D NL has a sharp peak.…”
Section: Introductionmentioning
confidence: 99%